Fragment screening libraries for the identification of protein hot spots and their minimal binding pharmacophores. Issue 1 (29th November 2022) - Whitehouse, Rebecca L.; Alwan, Wesam S.; Ilyichova, Olga V.; Taylor, Ashley J.; Chandrashekaran, Indu R.; Mohanty, Biswaranjan; Doak, Bradley C.; Scanlon, Martin J.
Abstract : Small molecule interaction hotpots were identified by screening small, low complexity fragments using X-ray crystallography. These hot spots include cryptic pockets and provide pharmacophore mapping that may be used in structure-based drug design. Abstract : Fragment-based drug design relies heavily on structural information for the elaboration and optimisation of hits. The ability to identify neighbouring binding hot spots, energetically favourable interactions and conserved binding motifs in protein structures through X-ray crystallography can inform the evolution of fragments into lead-like compounds through structure-based design. The composition of fragment libraries can be designed and curated to fit this purpose and herein, we describe and compare screening libraries containing compounds comprising between 2 and 18 heavy atoms. We evaluate the properties of the compounds in these libraries and assess their ability to probe protein surfaces for binding hot spots.